The Regional Language Revitalization Programme of the Balai Bahasa Provinsi Bali in Efforts to Maintain the Balinese Language at the Junior High School Level in Denpasar City - Ni Putu Diana Sari; I Ketut Paramarta; I Wayan Rasna (International Journal of Science and Society, 2026)
This study aims to describe the implementation of the Regional Language Revitalization Program by the Bali Provincial Language Office in maintaining the Balinese language among junior high school students in Denpasar City. This study employed a qualitative approach with data collected through interviews, observations, and document analysis. The results show that the implementation of the RBD program is carried out systematically through master teacher training, knowledge dissemination, and appreciative activities such as the Festival Tunas Bahasa Ibu (FTBI). The implementation contributes to the expansion of Balinese language use in both classroom learning and school activities. The program implementation also reveals several challenges, including limited instructional time, variations in teacher competence, and differences in institutional support across schools. Evaluation findings indicate that program effectiveness is determined by the integration of policies into the school curriculum and the consistency of stakeholder support. The RBD program demonstrates a transformative character, as reflected in changes in students’ attitudes and increased participation in using the Balinese language as part of their cultural identity. The sustainability of the program is influenced by the synergy between policy, institutional support, and learning practices that are internalized within school culture. This study confirms that maintaining the Balinese language through the RBD program requires a holistic, integrated, and sustainable approach to develop an adaptive linguistic ecosystem within the educational environment.